Valores referenciales de la hemoglobina corpuscular media en la población estudiantil masculina de 12 - 19 años de los Colegios Fiscales de la ciudad de Loja - Iñiguez López, César Arturo (2010)
The reference values are a set of measurable quantities either from individuals or groups an individual who is in a defined health status, to establish reference intervals is essential to use a representative sample of the population to which want to quantify. In the clinical laboratory are required to implement baseline reference intervals, these changes should be determined when analytical procedures or pre-analytical, is introducing a new procedure or when considering that exist are not appropriate for the population reference, as suggested by the ISO 15189 standard. The career of Clinical Laboratory, National University of Loja has designed the larger project called "Reference Values for haematological indices in the student population of 12 to 19 years for public schools of the city of Loja" addressing a teenager from the urban region due to lack of blood standardized values of the region, being necessary to establish reference values then, I have taken the "Mean Corpuscular Hemoglobin in the male student population of 12 to 19 years in the public schools of the city of Loja" as the objective essential to assist in the investigation and thereby help to obtain reference values of our area of influence. In this study we worked with a sample of 524 male students aged 12 to 19 years of public schools in the city of Loja by a random drawing and a percentage breakdown obtained the number of students from each school who would be part of research, the method used for this research study was a descriptive cross-sectional approach where interviews were conducted for the selection of the young participants, for students and parents in this way to have your approval. In addition, preanalytical and analytical protocols used in laboratory tests and recording forms and reporting of results. This research work is oriented to obtain standardization of reference values of mean corpuscular hemoglobin in male adolescents 12 to 19 years of public schools in the city of Loja and likewise develop a database, created in the EPI-INFO 6, which is to introduce the results of Hematology apparently healthy adolescents who entered the investigation, ultimately obtaining the following results for Mean Corpuscular Hemoglobin 26.7-31.9 pg. Subsequently disseminated the results to the authorities of the Department of Human Health and Clinical Laboratory Carrera, teachers of the Department of Human Health and the race, Rectors of colleges that were part of the study and career students and area health, in addition to the general public who went to Antonio Peña Celi Auditorium on April 30, 2010 at 17:00 pm